Children's perception of emotion in music : a cross-cultural study - Okhovat Poudeh, Azadeh (2015)
Previous research revealed that Western lullabies and children’s songs are mostly in the major mode, and children demonstrate a positive-major/negative-minor connotation that conforms to the conventional stereotype. The aim in this current study is to analyze the same topic in Finland and Iran where most lullabies are in the minor mode. The overarching question addressed is whether or not cultural background and the music mode, a child tends to be exposed to early in life affects later emotional responses to different music modes. Quantitative data was obtained from 5-8-year old children (n=44) and mothers (n=39) in mentioned countries. Background questionnaire and questions about twelve Finnish and Iranian music excerpts representing two modes and three genres were asked from participants. The main significant results show that Iranian children feel more positive (happy or relaxed) in response to the minor music than Finnish children, while Iranian and Finnish mothers both feel contentment in response to minor. In addition, unlike the Finns, Iranian children prefer to listen to the minor mode. These results demonstrate important effects of early music exposure on later emotional responses to music. Moreover, in this study, music familiarity and music preferences were assessed in both nationalities.